2018
DOI: 10.1136/gutjnl-2017-314722
|View full text |Cite
|
Sign up to set email alerts
|

Modern diagnosis of GERD: the Lyon Consensus

Abstract: Clinical history, questionnaire data and response to antisecretory therapy are insufficient to make a conclusive diagnosis of GERD in isolation, but are of value in determining need for further investigation. Conclusive evidence for reflux on oesophageal testing include advanced grade erosive oesophagitis (LA grades C and D), long-segment Barrett’s mucosa or peptic strictures on endoscopy or distal oesophageal acid exposure time (AET) >6% on ambulatory pH or pH-impedance monitoring. A normal endoscopy does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
1,293
3
159

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 1,122 publications
(1,626 citation statements)
references
References 160 publications
17
1,293
3
159
Order By: Relevance
“…8 Mean nocturnal baseline impedance (MNBI) was the averaged baseline impedance calculated at the 3-cm and 5-cm channels at three stable nocturnal time periods 8 Mean nocturnal baseline impedance (MNBI) was the averaged baseline impedance calculated at the 3-cm and 5-cm channels at three stable nocturnal time periods…”
Section: Ambulatory Ph-impedance Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Mean nocturnal baseline impedance (MNBI) was the averaged baseline impedance calculated at the 3-cm and 5-cm channels at three stable nocturnal time periods 8 Mean nocturnal baseline impedance (MNBI) was the averaged baseline impedance calculated at the 3-cm and 5-cm channels at three stable nocturnal time periods…”
Section: Ambulatory Ph-impedance Testingmentioning
confidence: 99%
“…2 Inadequate refluxate clearance can involve various elements of esophageal motor function, including inability to initiate primary or secondary peristalsis, impaired or absent peristaltic sequences, and abnormal esophagogastric junction (EGJ) morphology. 7,8 Hypomotility patterns on esophageal HRM, including fragmented peristalsis, ineffective esophageal motility (IEM), and absent contractility, have been linked to abnormal reflux clearance. 7,8 Hypomotility patterns on esophageal HRM, including fragmented peristalsis, ineffective esophageal motility (IEM), and absent contractility, have been linked to abnormal reflux clearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Linear regression analysis of the impedance-pH parameters showed that only the initial number of SGBs was significantly associated with percentage change in VAS score (Table 1). The median total number of reflux episodes was 49 (31-82) episodes, in which those of acid reflux was 37 (16-55) episodes.…”
Section: Objective Measurements; Impedance-ph Monitoringmentioning
confidence: 99%
“…В.Н. Чернобрового) [7]. Для ендоскопічної оцінки ступеня ураження стравоходу використовували Лос-Анджелеську (LA) класифіка-цію (1998).…”
Section: матеріали та методиunclassified